Reinforced-concrete Bond with Brine and Olive Oil Mill Wastewater - Husein A. Alzgool; Ahmad S. Alfraihat; Hadeel Alzghool (Civil Engineering Journal, 2022)
Since the interaction between the steel reinforcement and concrete directly controls the bond strength between them, poor bond performance results in a direct negative effect on the existing state of reinforced concrete structures. This bond is one of the most important factors affecting the strength of reinforced concrete. The bond strength is measured using the pull-out test. The present paper discusses the effect of the addition of brine and olive oil mill wastewaters to the reinforced concrete mixes. The main objective of this study is to determine the effect of brine wastewaters and olive oil mill wastewaters on the bond strength between steel and concrete when adding each of the admixtures to the concrete components. Pull-out tests were conducted on concrete mixes with additive contents of 2.5, 5, 7.5, 10, and 15 % by weight of water for each. It was found that the bonding strength of reinforced concrete specimens with an olive oil mill and brine wastewater improved and decreased by approximately 6–10% and 2–5%, respectively, if compared to the reference samples. These values were observed for mixes with additive contents of 7.5% for olive oil mill wastewaters and 10% for brine wastewaters. Doi: 10.28991/CEJ-2022-08-02-010 Full Text: PDF